An Analysis Of Code Mixing And Code Switching On Najwa Shihab Podcast “Susahnya Jadi Perempuan” (Catatan Najwa) - Situmorang, Korinthya Exaudia; Pasaribu, Tiara Kristina; Sembiring, Rony Arahta (Pascasarjana Universitas Negeri Makassar, 2023)
This research focuses on analyze the occurrence of code-mixing and code-switching in Najwa Shihab's podcast episode entitled